2015
DOI: 10.14260/jemds/2015/1993
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Fractures of Distal End Radius With Locking Compression Plate

Abstract: ABSTRACT:Fractures of distal end of radius continue to pose a therapeutic challenge. Intra articular and extra articular malalignment can lead to various complications like post-traumatic osteoarthrosis, decreased grip strength and endurance, as well as limited motion and carpal instability. Open reduction and internal fixation is indicated to address the unstable distal radius fractures and those with articular incongruity that cannot be anatomically reduced and maintained through external manipulation and li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
3
1
0
Order By: Relevance
“…16 In the present study, 6 (5.3%) and 2 (1.8%) patients had superficial infection and hypertrophic scar respectively while 1 (0.9%) patient had developed malunion. This is similar to the studies of Prasath et al, Maj Chahar et al and Chavhan et al [10][11][12] In our study, on the basis of demerit point score system of Gartland and Werley, 75 (69.4%) patients had excellent score while 24 (17.5%) and 15 (13.1%) patients had good and fair score respectively. No patient had poor score.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…16 In the present study, 6 (5.3%) and 2 (1.8%) patients had superficial infection and hypertrophic scar respectively while 1 (0.9%) patient had developed malunion. This is similar to the studies of Prasath et al, Maj Chahar et al and Chavhan et al [10][11][12] In our study, on the basis of demerit point score system of Gartland and Werley, 75 (69.4%) patients had excellent score while 24 (17.5%) and 15 (13.1%) patients had good and fair score respectively. No patient had poor score.…”
Section: Resultssupporting
confidence: 92%
“…This finding was like the studies of Prasath et al, Maj Chahar et al and Chavhan et al [10][11][12] Prasath et al prospective longitudinal study observed showed mean duration between the time of fracture and surgery was 3.3 days. 10 Maj Chahar et al prospective study showed 13 patients were operated within 5 days, 7 were operated within 10 days. 11 The average time interval between injury and surgery was 5.6 days.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Recent studies have emphasized that better methods of identifying and classifying distal radial fracture may direct the treating surgeon to alter the treatment and to adopt open reduction of these fractures in the proper circumstances [6] . In order to treat unstable distal Radius fractures and articular incongruities that cannot be anatomically reduced and maintained through external manipulation and ligamentotaxis, open reduction and internal fixation is indicated, provided that there is enough bone stock to allow for early range of motion [7] . A tiny buttress plate, like the one Ellis described, is routinely utilised as a fixation for volar marginal fractures since loss of reduction with displacement of the carpus is so common [8] .…”
Section: Introductionmentioning
confidence: 99%